Increased Serum Concentrations of High Mobility Group Box 1 (HMGB1) Protein in Children with Autism Spectrum Disorder - Gerasimos Makris; Giorgos Chouliaras; Filia Apostolakou; Charalabos Papageorgiou; George P. Chrousos; Ioannis Papassotiriou; Panagiota Pervanidou (MDPI AG, 2021)
High mobility group box 1 protein (HMGB1) has been suggested to be involved in the immune dysfunction and inflammation reported in autism spectrum disorder (ASD). We aimed to assess HMGB1 serum concentrations (SCs) in high-functioning ASD children compared to typically developing (TD) controls and to explore their associations with the autism spectrum quotient (AQ), the empathy quotient (EQ), and the systemizing quotient (SQ). The study involved 42 ASD children and 38 TD children, all-male, aged between 6.1 and 13.3 years old. HMGB1 SCs were measured by enzyme-linked immunosorbent assay (ELISA). Groups were comparable regarding age, general IQ, birth weight, and maternal age at birth. ASD children showed significantly higher HMGB1 SCs compared to TD children (1.25 ± 0.84 ng/mL versus 1.13 ± 0.79 ng/mL, respectively, p = 0.039). The Spearman's rho revealed that HMGB1 SCs were positively correlated with the AQ attention to detail subscale (rs = 0.46, p = 0.045) and with the SQ total score (rs = 0.42, p = 0.04) in the ASD group. These results show that HMGB1 serum concentrations are altered in ASD children, and suggest that inflammatory processes mediated by HMGB1 may be associated with specific cognitive features observed in ASD.